Environmental impact of non-certified versus certified (ASC) intensive Pangasius aquaculture in Vietnam, a comparison based on a statistically supported LCA. (December 2016) - Nhu, Trang T.; Schaubroeck, Thomas; Henriksson, Patrik J.G.; Bosma, Roel; Sorgeloos, Patrick; Dewulf, Jo
Abstract: Pangasius production in Vietnam is widely known as a success story in aquaculture, the fastest growing global food system because of its tremendous expansion by volume, value and the number of international markets to which Pangasius has been exported in recent years. While certification schemes are becoming significant features of international fish trade and marketing, an increasing number of Pangasius producers have followed at least one of the certification schemes recognised by international markets to incorporate environmental and social sustainability practices in aquaculture, typically the Pangasius Aquaculture Dialogue (PAD) scheme certified by the Aquaculture Stewardship Council (ASC). An assessment of the environmental benefit of applying certification schemes on Pangasius production, however, is still needed. This article compared the environmental impact of ASC-certified versus non-ASC certified intensive Pangasius aquaculture, using a statistically supported LCA. We focused on both resource-related (water, land and total resources) and emissions-related (global warming, acidification, freshwater and marine eutrophication) categories. The ASC certification scheme was shown to be a good approach for determining adequate environmental sustainability, especially concerning emissions-related categories, in Pangasius production. However, the non-ASC certified farms, due to the large spread, the impact (e.g., water resources and freshwater eutrophication) was possibly lower for a certain farm. However, this result was not generally prominent. Further improvements in intensive Pangasius production to inspire certification schemes are proposed, e.g., making the implementation of certification schemes more affordable, well-oriented and facilitated; reducing consumed feed amounts and of the incorporated share in fishmeal, especially domestic fishmeal, etc. However, their implementation should be vetted with key stakeholders to assess their feasibility. Graphical abstract: Highlights: Life cycle assessment of non-ASC certified and ASC-certified Pangasius aquaculture. Environmental indicators: resource use, global warming, acidification, and eutrophication. ASC certification has a significantly lower impact on the above environmental indicators. ASC certification provides no clear benefit to water resource and freshwater eutrophication impacts. Further improvements for intensive Pangasius production are proposed. Abstract : The ASC certification scheme is shown to be a good approach for Pangasius production for generating adequate environmental sustainability, especially concerning emissions-related categories.